Study on the Effect of the Three-Dimensional Electrode in Degradation of Methylene Blue by Lithium Modified Rectorite - Jian Huang; Yin’an Ming; Ying Du; Yingru Wang; Ci’en Wang (Journal of Analytical Methods in Chemistry)
This study presents the electrochemical degradation of methylene blue (MB) wastewater in a synthetic solution using three-dimensional particle electrodes. The novel particle electrodes were fabricated in this work using the lithium modified rectorite (Li-REC). The adsorption property of the fabricated particle electrodes was studied in a series of experiments. The optimum electrochemical operating conditions of plate distance, cell voltage, and concentration of electrolyte were 2 cm, 9 V, and 0.06 mol L−1, respectively. It was also found that microwave irradiation can effectively improve the adsorption property and electrical property of the fabricated electrodes. In addition, the scanning electron microscope (SEM) of the fabricated electrodes was investigated. The experimental results revealed the order of adsorption property and electrical property of the fabricated electrodes. So, fabricated electrodes are not only of low cost and mass produced, but also efficient to achieve decolorization of MB solution.